Sistem Informasi Kas Kecil Pada PT. Carpotama Anugrah Sejati - Darmuji; M. Firman; Marya Ulpa (Journal of Applied Accounting And Business, 2020)
PT Carpotama Anugrah Sejati is acompany engaged in the SPPBE (LPG Bulk Filling and Transportation Station) in Jambi. The management of data on expenditures and entries in the petty cashier of PT Corpotama Anugrah Sejati is still done manually so that the performance in the process of managing expenditure and income data still not optimal. In order to be more optimal, it si necessary to have a web-based accounting information system. The purpose of this study is to design a petty cash information system in accordance with correct accounting standards. The method of data collection is done by interview, observation, documentation and analysis of the systems used by the company. The result of this research is to produce a web-based petty cash information system with the fluctuation method that makes it easy to record petty cash funds using cash flow diagrams, DFD, ERD and MySQL for data processing. The result of this research is that the existence of this petty cash system can produce more efficient and accurate recordingof petty cash funds